Selective Adsorption of Terrestrial Dissolved Organic Matter to Inorganic Surfaces Along a Boreal Inland Water Continuum. Issue 3 (20th March 2020) - Groeneveld, Marloes; Catalán, Núria; Attermeyer, Katrin; Hawkes, Jeffrey; Einarsdóttir, Karólína; Kothawala, Dolly; Bergquist, Jonas; Tranvik, Lars
Abstract: Different processes contribute to the loss or transformation of dissolved organic matter (DOM) and change DOM concentration and composition systematically along the inland water continuum. Substantial efforts have been made to estimate the importance of microbial and photochemical degradation for DOM concentration and composition and, to some extent, also DOM losses by flocculation, whereas the significance of DOM adsorption to inorganic surfaces has received less attention. Hence, knowledge on the possible extent of adsorption, its effect on DOM loads and composition and on where along the aquatic continuum it might be important, is currently limited or lacking altogether. Here we experimentally determine DOM adsorption onto mineral particles in freshwater ecosystems covering a water residence time gradient in boreal landscape Sweden. We hypothesized that adsorption would gradually decrease with increasing water residence time but actually found that DOM is highly susceptible to adsorption throughout the aquatic continuum. Mass spectrometry and fluorescence analysis on DOM suggest that freshly produced aquatic DOM is less susceptible to adsorption than more terrestrial material. Moreover, the percentage DOM adsorbed in the experiments greatly exceeds the actual adsorption taking place in boreal inland waters across all studied systems. These results illustrate the potential impact of mineral erosion, for example, as a result of agriculture, mining or forestry practices, on the availability, transport, and composition of organic carbon in inland waters. Plain Language Summary: Freshwaters are an important part of the global carbon cycle. They produce organic matter internally and receive large amounts of organic matter from the surrounding land. Within freshwaters, organic matter can be transported to the ocean, converted to carbon dioxide and methane, or buried in the sediment, depending on the chemical composition of the organic molecules and environmental conditions. One pathway toward burial is adsorption onto inorganic particles, such as clay, that may have entered the water by erosion. In this study, we added clay particles to 30 water samples collected throughout Sweden, from peats to very large lakes. We found that a large part of the organic matter could be adsorbed onto the clay and that molecules derived from land‐vegetation are more likely to be adsorbed than molecules produced in the water. As a result, adsorption to clay changes the composition of the organic matter in the water. We observed that the potential for adsorption exceeds the adsorption actually taking place in most natural systems. This implies that introduction of minerals by erosion, for example, as a result of agriculture, mining, or forestry practices, could affect the composition of organic matter and thereby its fate in the carbon cycle. Key Points: Adsorption to clay selectively removes terrestrial dissolved organic matter (DOM) Both DOM composition and water chemistry determine the percentage DOM adsorbed The percentage DOM adsorbed was not directly related to water residence time